Analisa Rasio Likuiditas Laporan Keuangan Pada Adira Dinamika Multi Finance Tbk - Dian Indah Sari (Universitas Bina Sarana Informatika, 2017)
The purpose of this study was to determine and identify the liquidity ratios that affect ability Adira Dinamika Multi Finance Tbk to meet the financial obligations associated with parties outside the company or creditors. In this study, the authors use three different types of data collection methods, namely the literature study (library research), non observation of behavior in the form of observational methods of financial statements issued by Adira Dinamika Multi Finance Tbk during the period 2014 and 2015 and the methods of deduction. Based on the calculation above it can be concluded as follows: Current Ratio or Current Ratio in 2015 increased by 2% from 2014. Quick Ratio or Acid Test Ratio in 2015 increased by 2% compared to the quick ratio in 2014. Cash ratio or Cash ratio in 2015 increased by 0.85 times compared to 2014. Cash Turn Over or ratio Cash Turn Over 2015 increased by 1.15 times compared to 2014. Benefits from the calculation of the liquidity ratio for Adira Dinamika Multi Finance Tbk, as a tool planning ahead, especially with regard to cash planning and debt as well as a trigger for the management to improve their performance.Keywords : Ratio Analysis, Financial Statements, Liquidity